The role of silicon in plant tissue culture - Sivanesan, Iyyakkannu; Park, Se Won (Frontiers in Plant Science, 2014)
Growth and morphogenesis of in vitro cultures of plant cells, tissues and organs are greatly influenced by the composition of the culture medium. Mineral nutrients are necessary for the growth and development of plants. Several morpho-physiological disorders such as hooked leaves, hyperhydricity, fasciation and shoot tip necrosis are often associated with the concentration of inorganic nutrient in the tissue culture medium. Silicon (Si) is the most abundant mineral element in the soil. The application of Si has been demonstrated to be beneficial for growth, development and yield of various plants and to alleviate various stresses including nutrient imbalance. Addition of Si to the tissue culture medium improves organogenesis, embryogenesis, growth traits, morphological, anatomical and physiological characteristics of leaves, enhances tolerance to low temperature and salinity, protects cells and against metal toxicity, prevents oxidative phenolic browning and reduces the incidence of hyperhydricity in various plants. Therefore, Si possesses considerable potential for application in a wide range of plant tissue culture studies such as cryopreservation, organogenesis, micropropagation, somatic embryogenesis and secondary metabolites production.